2020
DOI: 10.1002/ps.5724
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of attractants from the pupae of three lepidopteran species for the parasitoid Chouioia cunea Yang

Abstract: BACKGROUND Chouioia cunea Yang (Hymenoptera: Eulophidae) is a parasitic wasp and natural enemy of several lepidopteran pests during their pupal stage. The volatiles from pupae of three hosts, Hyphantria cunea (Arctiidae), Antheraea pernyi (Saturniidae) and Lymantria dispar (Erebidae), were analyzed and compared to elucidate the chemical cues used by C. cunea to locate its hosts. RESULTS The attraction of C. cunea to H. cunea pupae has no obvious association with the types of plant leaves consumed by H. cunea b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…These HIPVs, which have been reported in other plants (Sanchez et al, 2012;Zhou et al, 2015), are usually exploited by arthropods in plant selection (Bernasconi et al, 1998;Halitschke et al, 2008). Indeed, 1-Dodecene has been described as repellent of phytophagous insects but as attractant of natural enemies (Li et al, 2020). The production of this volatile increased in the two Citrus spp.…”
Section: Discussionmentioning
confidence: 86%
“…These HIPVs, which have been reported in other plants (Sanchez et al, 2012;Zhou et al, 2015), are usually exploited by arthropods in plant selection (Bernasconi et al, 1998;Halitschke et al, 2008). Indeed, 1-Dodecene has been described as repellent of phytophagous insects but as attractant of natural enemies (Li et al, 2020). The production of this volatile increased in the two Citrus spp.…”
Section: Discussionmentioning
confidence: 86%
“…In a previous study, we showed that 1‐dodecene was a strong attractant of C. cunea females. Moreover, we identified 1‐dodecene in three host species of C. cunea , such as the pupae of Hyphantria cunea , A. pernyi and L. dispar 24 . The volatile emissions of some flowers contain 1‐dodecene, 27 which might attract pollinators and behave as a synomone, benefiting both the emitter and the receiver.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, we identified 1-dodecene in three host species of C. cunea, such as the pupae of Hyphantria cunea, A. pernyi and L. dispar. 24 The volatile emissions of some flowers contain 1-dodecene, 27 which might attract pollinators and behave as a synomone, benefiting both the emitter and the receiver. Sometimes 1-dodecene is an insect repellant in some plants, acting as an allomone that only benefits the emitter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations